CONCEPTS, THEORETICAL AND METHODOLOGICAL APPROACHES TO The POLITICAL PROCESSES (World Bulletin of Social Sciences, 2022)
The article presents the concept of the political process, its peculiarities, the views of world scholars on political processes from a political point of view, the classical approaches. The current state of political processes is comparatively analyzed on the basis of materials from independent Uzbekistan and neighboring countries.